Producing Effective and Clean Coke for Household Combustion Activities to Reduce Gaseous Pollutant Emissions - Shoujun Liu; Ju Shangguan; Song Yang; Wenguang Du; Xudong Yan; Kaixia Zhang (Journal of Chemistry)
Nowadays, the gaseous pollutant emissions, including particulate matter (PM), sulfur dioxide (SO2), and nitrogen oxide (NOx) from household coal combustion, cause great threat to environment and public health by contributing to severe haze in China. Particularly, a clean coke free of the major pollutants precursors (sulfur and nitrogen compounds) by sulfur fixation and denitrification has been deemed as an effective strategy to reducing pollutants. In this paper, a preprocessed coke was prepared by co-pyrolysis of high-sulfur coal with the assistance of calcium-based and iron-based complexes at high temperature. The results show that high-temperature co-pyrolysis could remove the volatile compounds that are major precursors for the formation of gaseous pollutants from the raw coal. During the coking process, the sulfur can be removed by being fixed in the form of CaS in presence of a Ca-based complex, which could be beneficial for the CaSO4 during the coke combustion. The volatile nitrogen is transferred to the gas phase with the addition of Fe-based complexes, which effectively reduce the residual nitrogen in coke. As a result, Ca-based additives captured the released SO2 and formed CaSO4 during the combustion process. In addition, in the presence of Fe-based complexes, both char and CO react with NOx to form N2, which leads to a reduction in NOx emissions during combustion. Additionally, the replacement of current residential coal with a new type of clean coke is a facile method for reducing gaseous pollutant emissions from household activities to protect the atmospheric environment. The average emission factors (EFs) of PM, SO2, and NOx for the prepared clean coke were small during combustion and were much lower than the EFs of the tested raw coal, semicoke, and briquettes.